2020
DOI: 10.18483/ijsci.2305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kaolin Consumption on Serum Heavy Metal Levels of Pregnant Women

Abstract: Geophagy is the consumption of earth materials across several cultures in many continents. For various reasons, consumption of kaolin is common among pregnant women in Nigeria. This earth material is known to contain heavy metals. This study was carried out to determine the effect of kaolin consumption on some heavy metal levels in pregnant women attending antenatal clinic in a Teaching Hospital in the south east Nigeria. A total of eighty pregnant women recruited for this study were grouped as follows; Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Cadmium (Cd) and Hg were observed to bio-accumulate in the liver ( 92 ). Similarly, serum levels of Pb and varying concentrations of other heavy metals have been found ( 93 , 94 ), confirming that toxic heavy metals can be absorbed during toxic clay consumption. Ekosse et al ( 43 ) inferred limited health threats in a study in which they observed low bioavailability of heavy metals in gastrointestinal tract simulation.…”
Section: Prevalence Etiology and Management Of Geophagymentioning
confidence: 76%
“…Cadmium (Cd) and Hg were observed to bio-accumulate in the liver ( 92 ). Similarly, serum levels of Pb and varying concentrations of other heavy metals have been found ( 93 , 94 ), confirming that toxic heavy metals can be absorbed during toxic clay consumption. Ekosse et al ( 43 ) inferred limited health threats in a study in which they observed low bioavailability of heavy metals in gastrointestinal tract simulation.…”
Section: Prevalence Etiology and Management Of Geophagymentioning
confidence: 76%
“…Msoffe et al (2019) indicated that pregnant women in Tanzania and their babies are potentially exposed to toxic levels of As, Al, Ba, Cd, Ni, and Pb. The practice of geophagia during pregnancy is also associated high serum level of the heavy metals, as shown in a study conducted in Nigeria among geophagic pregnant women (Akah et al, 2020). Zeigbo et al (2020) also showed that geophagia may predispose pregnant women to gestational diabetes, electrolytes imbalance and reduced intestinal enzymes activities.…”
Section: Discussionmentioning
confidence: 93%
“…Ingestion of soils rich in high amounts of Fe could be harmful to pregnant women and their unborn child (Abrahams et al, 2006). Carmichael et al (2003) and Akah et al (2020) also stated that the practice of geophagia during pregnancy could be a risk factor for lead toxicity in infants. Gundacker et al (2017) reported that soils ingested by pregnant women in some parts Democratic Republic of Congo contained substantial amount of lead, which could lead to prenatal lead exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of unregulated and continuous kaolin consumption in pregnancy may manifest as gestational diabetes and its associated complications. The mechanism by which kaolin elevates plasma glucose is not known, however, previous findings revealed that some heavy metals were elevated in pregnant women on kaolin [20]. Heavy metals especially lead and arsenic had demonstrated inhibitory activities on insulin and were capable of inactivating over 200 enzymes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Though, clinical relevance of low serum amylase is poorly understood, animal and cellular studies regarding the relationship with endocrine and exocrine pancreas have shown that insulin secretion affected the basal and stimulatory amylase secretion via islet of acinar axis, and there was negative association between serum amylase and heavy metals [26]. High concentration of some heavy metals in geophargic pregnant women has been documented [20], and in biological systems heavy metals have been reported to inactivate enzymes, and affect cellular organelles and components [27].…”
Section: Discussionmentioning
confidence: 99%